2022
DOI: 10.1161/circulationaha.122.059678
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin and the 2021 AHA/ACC/ASE/CHEST/SAEM/SCCT/SCMR Guidelines for the Evaluation and Diagnosis of Acute Chest Pain

Abstract: The 2021 American Heart Association/American College of Cardiology/American Society of Echocardiography/American College of Chest Physicians/Society for Academic Emergency Medicine/Society of Cardiovascular Computed Tomography/Society for Cardiovascular Magnetic Resonance guidelines for the evaluation and diagnosis of acute chest pain make important recommendations that include the recognition of high-sensitivity cardiac troponin (hs-cTn) as the preferred biomarker, endorsement of 99th percentile upper referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…Blood‐based biomarkers of neurodegeneration are potentially critical tools in the global fight against Alzheimer's disease (AD) and related dementias 1 . As neurodegenerative biomarkers, these analytes are not necessarily specific for a single pathophysiology but, as markers of neuronal injury and death, may provide predictive and staging information across dementia subtypes, analogous to the broad use of high‐sensitivity troponin as a biomarker of myocyte damage in cardiac disease 2 . Moreover, if shown to predict future incidence of dementia among individuals at risk, biomarkers of preclinical disease could assist in recruitment to future preventive trials that may enable disease‐modifying intervention prior to a critical loss of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Blood‐based biomarkers of neurodegeneration are potentially critical tools in the global fight against Alzheimer's disease (AD) and related dementias 1 . As neurodegenerative biomarkers, these analytes are not necessarily specific for a single pathophysiology but, as markers of neuronal injury and death, may provide predictive and staging information across dementia subtypes, analogous to the broad use of high‐sensitivity troponin as a biomarker of myocyte damage in cardiac disease 2 . Moreover, if shown to predict future incidence of dementia among individuals at risk, biomarkers of preclinical disease could assist in recruitment to future preventive trials that may enable disease‐modifying intervention prior to a critical loss of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These data will dramatically increase the sample size for analyzing the diagnosis threshold for AMI. For example, the 2022 American Heart Association/American College of Cardiology guidelines for chest pain diagnosis indicated detecting changes in troponin levels in the very early stage of AMI is difficult [ 37 ]. This is due, in part, to the lack of sufficient sample size.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] hs-troponin I is strongly associated with ischemic heart disease and other markers of end organ damage. 6,11,13 hs-troponin assays are the preferred biomarker by the American Heart Association for the detection of myocardial injury, 42 and both hs-troponin T and hs-troponin I are indicative of cardiomyocyte injury or necrosis. Prior studies have demonstrated that hs-troponin T and hs-troponin I are strongly associated with major adverse cardiovascular events, mortality, and rapid progression to symptomatic heart failure in asymptomatic adults.…”
Section: Table 3 Associations* (Or [95% Ci]) Of Clinical Categories O...mentioning
confidence: 99%